12.12: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/12.12.E1 12.12.E1] || [[Item:Q4226|<math>\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{\mu-1}\paraU@{a}{t}\diff{t} = \frac{\sqrt{\pi}2^{-\frac{1}{2}(\mu+a+\frac{1}{2})}\EulerGamma@{\mu}}{\EulerGamma@{\frac{1}{2}(\mu+a+\frac{3}{2})}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{\mu-1}\paraU@{a}{t}\diff{t} = \frac{\sqrt{\pi}2^{-\frac{1}{2}(\mu+a+\frac{1}{2})}\EulerGamma@{\mu}}{\EulerGamma@{\frac{1}{2}(\mu+a+\frac{3}{2})}}</syntaxhighlight> || <math>\realpart@@{\mu} > 0, \realpart@@{(\mu)} > 0, \realpart@@{(\frac{1}{2}(\mu+a+\frac{3}{2}))} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(-(1)/(4)*(t)^(2))*(t)^(mu - 1)* CylinderU(a, t), t = 0..infinity) = (sqrt(Pi)*(2)^(-(1)/(2)*(mu + a +(1)/(2)))* GAMMA(mu))/(GAMMA((1)/(2)*(mu + a +(3)/(2))))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[-Divide[1,4]*(t)^(2)]*(t)^(\[Mu]- 1)* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == Divide[Sqrt[Pi]*(2)^(-Divide[1,2]*(\[Mu]+ a +Divide[1,2]))* Gamma[\[Mu]],Gamma[Divide[1,2]*(\[Mu]+ a +Divide[3,2])]]</syntaxhighlight> || Successful || Aborted || - || Skipped - Because timed out
| [https://dlmf.nist.gov/12.12.E1 12.12.E1] || <math qid="Q4226">\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{\mu-1}\paraU@{a}{t}\diff{t} = \frac{\sqrt{\pi}2^{-\frac{1}{2}(\mu+a+\frac{1}{2})}\EulerGamma@{\mu}}{\EulerGamma@{\frac{1}{2}(\mu+a+\frac{3}{2})}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{\mu-1}\paraU@{a}{t}\diff{t} = \frac{\sqrt{\pi}2^{-\frac{1}{2}(\mu+a+\frac{1}{2})}\EulerGamma@{\mu}}{\EulerGamma@{\frac{1}{2}(\mu+a+\frac{3}{2})}}</syntaxhighlight> || <math>\realpart@@{\mu} > 0, \realpart@@{(\mu)} > 0, \realpart@@{(\frac{1}{2}(\mu+a+\frac{3}{2}))} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(-(1)/(4)*(t)^(2))*(t)^(mu - 1)* CylinderU(a, t), t = 0..infinity) = (sqrt(Pi)*(2)^(-(1)/(2)*(mu + a +(1)/(2)))* GAMMA(mu))/(GAMMA((1)/(2)*(mu + a +(3)/(2))))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[-Divide[1,4]*(t)^(2)]*(t)^(\[Mu]- 1)* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == Divide[Sqrt[Pi]*(2)^(-Divide[1,2]*(\[Mu]+ a +Divide[1,2]))* Gamma[\[Mu]],Gamma[Divide[1,2]*(\[Mu]+ a +Divide[3,2])]]</syntaxhighlight> || Successful || Aborted || - || Skipped - Because timed out
|-  
|-  
| [https://dlmf.nist.gov/12.12.E2 12.12.E2] || [[Item:Q4227|<math>\int_{0}^{\infty}e^{-\frac{3}{4}t^{2}}t^{-a-\frac{3}{2}}\paraU@{a}{t}\diff{t} = 2^{\frac{1}{4}+\frac{1}{2}a}\EulerGamma@{-a-\tfrac{1}{2}}\cos@{(\tfrac{1}{4}a+\tfrac{1}{8})\pi}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}e^{-\frac{3}{4}t^{2}}t^{-a-\frac{3}{2}}\paraU@{a}{t}\diff{t} = 2^{\frac{1}{4}+\frac{1}{2}a}\EulerGamma@{-a-\tfrac{1}{2}}\cos@{(\tfrac{1}{4}a+\tfrac{1}{8})\pi}</syntaxhighlight> || <math>\realpart@@{a} < -\tfrac{1}{2}, \realpart@@{(-a-\tfrac{1}{2})} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(-(3)/(4)*(t)^(2))*(t)^(- a -(3)/(2))* CylinderU(a, t), t = 0..infinity) = (2)^((1)/(4)+(1)/(2)*a)* GAMMA(- a -(1)/(2))*cos(((1)/(4)*a +(1)/(8))*Pi)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[-Divide[3,4]*(t)^(2)]*(t)^(- a -Divide[3,2])* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == (2)^(Divide[1,4]+Divide[1,2]*a)* Gamma[- a -Divide[1,2]]*Cos[(Divide[1,4]*a +Divide[1,8])*Pi]</syntaxhighlight> || Failure || Failure || Skipped - Because timed out || Successful [Tested: 2]
| [https://dlmf.nist.gov/12.12.E2 12.12.E2] || <math qid="Q4227">\int_{0}^{\infty}e^{-\frac{3}{4}t^{2}}t^{-a-\frac{3}{2}}\paraU@{a}{t}\diff{t} = 2^{\frac{1}{4}+\frac{1}{2}a}\EulerGamma@{-a-\tfrac{1}{2}}\cos@{(\tfrac{1}{4}a+\tfrac{1}{8})\pi}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}e^{-\frac{3}{4}t^{2}}t^{-a-\frac{3}{2}}\paraU@{a}{t}\diff{t} = 2^{\frac{1}{4}+\frac{1}{2}a}\EulerGamma@{-a-\tfrac{1}{2}}\cos@{(\tfrac{1}{4}a+\tfrac{1}{8})\pi}</syntaxhighlight> || <math>\realpart@@{a} < -\tfrac{1}{2}, \realpart@@{(-a-\tfrac{1}{2})} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(-(3)/(4)*(t)^(2))*(t)^(- a -(3)/(2))* CylinderU(a, t), t = 0..infinity) = (2)^((1)/(4)+(1)/(2)*a)* GAMMA(- a -(1)/(2))*cos(((1)/(4)*a +(1)/(8))*Pi)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[-Divide[3,4]*(t)^(2)]*(t)^(- a -Divide[3,2])* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == (2)^(Divide[1,4]+Divide[1,2]*a)* Gamma[- a -Divide[1,2]]*Cos[(Divide[1,4]*a +Divide[1,8])*Pi]</syntaxhighlight> || Failure || Failure || Skipped - Because timed out || Successful [Tested: 2]
|-  
|-  
| [https://dlmf.nist.gov/12.12.E3 12.12.E3] || [[Item:Q4228|<math>\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{-a-\frac{1}{2}}(x^{2}+t^{2})^{-1}\paraU@{a}{t}\diff{t} = \sqrt{\pi/2}\EulerGamma@{\tfrac{1}{2}-a}x^{-a-\frac{3}{2}}e^{\frac{1}{4}x^{2}}\paraU@{-a}{x}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{-a-\frac{1}{2}}(x^{2}+t^{2})^{-1}\paraU@{a}{t}\diff{t} = \sqrt{\pi/2}\EulerGamma@{\tfrac{1}{2}-a}x^{-a-\frac{3}{2}}e^{\frac{1}{4}x^{2}}\paraU@{-a}{x}</syntaxhighlight> || <math>x > 0, \realpart@@{a} < \tfrac{1}{2}, \realpart@@{(\tfrac{1}{2}-a)} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(-(1)/(4)*(t)^(2))*(t)^(- a -(1)/(2))*((x)^(2)+ (t)^(2))^(- 1)* CylinderU(a, t), t = 0..infinity) = sqrt(Pi/2)*GAMMA((1)/(2)- a)*(x)^(- a -(3)/(2))* exp((1)/(4)*(x)^(2))*CylinderU(- a, x)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[-Divide[1,4]*(t)^(2)]*(t)^(- a -Divide[1,2])*((x)^(2)+ (t)^(2))^(- 1)* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == Sqrt[Pi/2]*Gamma[Divide[1,2]- a]*(x)^(- a -Divide[3,2])* Exp[Divide[1,4]*(x)^(2)]*ParabolicCylinderD[- 1/2 -(- a), x]</syntaxhighlight> || Failure || Aborted || Skipped - Because timed out || Skipped - Because timed out
| [https://dlmf.nist.gov/12.12.E3 12.12.E3] || <math qid="Q4228">\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{-a-\frac{1}{2}}(x^{2}+t^{2})^{-1}\paraU@{a}{t}\diff{t} = \sqrt{\pi/2}\EulerGamma@{\tfrac{1}{2}-a}x^{-a-\frac{3}{2}}e^{\frac{1}{4}x^{2}}\paraU@{-a}{x}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{-a-\frac{1}{2}}(x^{2}+t^{2})^{-1}\paraU@{a}{t}\diff{t} = \sqrt{\pi/2}\EulerGamma@{\tfrac{1}{2}-a}x^{-a-\frac{3}{2}}e^{\frac{1}{4}x^{2}}\paraU@{-a}{x}</syntaxhighlight> || <math>x > 0, \realpart@@{a} < \tfrac{1}{2}, \realpart@@{(\tfrac{1}{2}-a)} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(-(1)/(4)*(t)^(2))*(t)^(- a -(1)/(2))*((x)^(2)+ (t)^(2))^(- 1)* CylinderU(a, t), t = 0..infinity) = sqrt(Pi/2)*GAMMA((1)/(2)- a)*(x)^(- a -(3)/(2))* exp((1)/(4)*(x)^(2))*CylinderU(- a, x)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[-Divide[1,4]*(t)^(2)]*(t)^(- a -Divide[1,2])*((x)^(2)+ (t)^(2))^(- 1)* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == Sqrt[Pi/2]*Gamma[Divide[1,2]- a]*(x)^(- a -Divide[3,2])* Exp[Divide[1,4]*(x)^(2)]*ParabolicCylinderD[- 1/2 -(- a), x]</syntaxhighlight> || Failure || Aborted || Skipped - Because timed out || Skipped - Because timed out
|}
|}
</div>
</div>

Latest revision as of 11:31, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
12.12.E1 0 e - 1 4 t 2 t μ - 1 U ( a , t ) d t = π 2 - 1 2 ( μ + a + 1 2 ) Γ ( μ ) Γ ( 1 2 ( μ + a + 3 2 ) ) superscript subscript 0 superscript 𝑒 1 4 superscript 𝑡 2 superscript 𝑡 𝜇 1 parabolic-U 𝑎 𝑡 𝑡 𝜋 superscript 2 1 2 𝜇 𝑎 1 2 Euler-Gamma 𝜇 Euler-Gamma 1 2 𝜇 𝑎 3 2 {\displaystyle{\displaystyle\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{\mu-1}U% \left(a,t\right)\mathrm{d}t=\frac{\sqrt{\pi}2^{-\frac{1}{2}(\mu+a+\frac{1}{2})% }\Gamma\left(\mu\right)}{\Gamma\left(\frac{1}{2}(\mu+a+\frac{3}{2})\right)}}}
\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{\mu-1}\paraU@{a}{t}\diff{t} = \frac{\sqrt{\pi}2^{-\frac{1}{2}(\mu+a+\frac{1}{2})}\EulerGamma@{\mu}}{\EulerGamma@{\frac{1}{2}(\mu+a+\frac{3}{2})}}
μ > 0 , ( μ ) > 0 , ( 1 2 ( μ + a + 3 2 ) ) > 0 formulae-sequence 𝜇 0 formulae-sequence 𝜇 0 1 2 𝜇 𝑎 3 2 0 {\displaystyle{\displaystyle\Re\mu>0,\Re(\mu)>0,\Re(\frac{1}{2}(\mu+a+\frac{3}% {2}))>0}}
int(exp(-(1)/(4)*(t)^(2))*(t)^(mu - 1)* CylinderU(a, t), t = 0..infinity) = (sqrt(Pi)*(2)^(-(1)/(2)*(mu + a +(1)/(2)))* GAMMA(mu))/(GAMMA((1)/(2)*(mu + a +(3)/(2))))
Integrate[Exp[-Divide[1,4]*(t)^(2)]*(t)^(\[Mu]- 1)* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == Divide[Sqrt[Pi]*(2)^(-Divide[1,2]*(\[Mu]+ a +Divide[1,2]))* Gamma[\[Mu]],Gamma[Divide[1,2]*(\[Mu]+ a +Divide[3,2])]]
Successful Aborted - Skipped - Because timed out
12.12.E2 0 e - 3 4 t 2 t - a - 3 2 U ( a , t ) d t = 2 1 4 + 1 2 a Γ ( - a - 1 2 ) cos ( ( 1 4 a + 1 8 ) π ) superscript subscript 0 superscript 𝑒 3 4 superscript 𝑡 2 superscript 𝑡 𝑎 3 2 parabolic-U 𝑎 𝑡 𝑡 superscript 2 1 4 1 2 𝑎 Euler-Gamma 𝑎 1 2 1 4 𝑎 1 8 𝜋 {\displaystyle{\displaystyle\int_{0}^{\infty}e^{-\frac{3}{4}t^{2}}t^{-a-\frac{% 3}{2}}U\left(a,t\right)\mathrm{d}t=2^{\frac{1}{4}+\frac{1}{2}a}\Gamma\left(-a-% \tfrac{1}{2}\right)\cos\left((\tfrac{1}{4}a+\tfrac{1}{8})\pi\right)}}
\int_{0}^{\infty}e^{-\frac{3}{4}t^{2}}t^{-a-\frac{3}{2}}\paraU@{a}{t}\diff{t} = 2^{\frac{1}{4}+\frac{1}{2}a}\EulerGamma@{-a-\tfrac{1}{2}}\cos@{(\tfrac{1}{4}a+\tfrac{1}{8})\pi}
a < - 1 2 , ( - a - 1 2 ) > 0 formulae-sequence 𝑎 1 2 𝑎 1 2 0 {\displaystyle{\displaystyle\Re a<-\tfrac{1}{2},\Re(-a-\tfrac{1}{2})>0}}
int(exp(-(3)/(4)*(t)^(2))*(t)^(- a -(3)/(2))* CylinderU(a, t), t = 0..infinity) = (2)^((1)/(4)+(1)/(2)*a)* GAMMA(- a -(1)/(2))*cos(((1)/(4)*a +(1)/(8))*Pi)
Integrate[Exp[-Divide[3,4]*(t)^(2)]*(t)^(- a -Divide[3,2])* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == (2)^(Divide[1,4]+Divide[1,2]*a)* Gamma[- a -Divide[1,2]]*Cos[(Divide[1,4]*a +Divide[1,8])*Pi]
Failure Failure Skipped - Because timed out Successful [Tested: 2]
12.12.E3 0 e - 1 4 t 2 t - a - 1 2 ( x 2 + t 2 ) - 1 U ( a , t ) d t = π / 2 Γ ( 1 2 - a ) x - a - 3 2 e 1 4 x 2 U ( - a , x ) superscript subscript 0 superscript 𝑒 1 4 superscript 𝑡 2 superscript 𝑡 𝑎 1 2 superscript superscript 𝑥 2 superscript 𝑡 2 1 parabolic-U 𝑎 𝑡 𝑡 𝜋 2 Euler-Gamma 1 2 𝑎 superscript 𝑥 𝑎 3 2 superscript 𝑒 1 4 superscript 𝑥 2 parabolic-U 𝑎 𝑥 {\displaystyle{\displaystyle\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{-a-\frac{% 1}{2}}(x^{2}+t^{2})^{-1}U\left(a,t\right)\mathrm{d}t=\sqrt{\pi/2}\Gamma\left(% \tfrac{1}{2}-a\right)x^{-a-\frac{3}{2}}e^{\frac{1}{4}x^{2}}U\left(-a,x\right)}}
\int_{0}^{\infty}e^{-\frac{1}{4}t^{2}}t^{-a-\frac{1}{2}}(x^{2}+t^{2})^{-1}\paraU@{a}{t}\diff{t} = \sqrt{\pi/2}\EulerGamma@{\tfrac{1}{2}-a}x^{-a-\frac{3}{2}}e^{\frac{1}{4}x^{2}}\paraU@{-a}{x}
x > 0 , a < 1 2 , ( 1 2 - a ) > 0 formulae-sequence 𝑥 0 formulae-sequence 𝑎 1 2 1 2 𝑎 0 {\displaystyle{\displaystyle x>0,\Re a<\tfrac{1}{2},\Re(\tfrac{1}{2}-a)>0}}
int(exp(-(1)/(4)*(t)^(2))*(t)^(- a -(1)/(2))*((x)^(2)+ (t)^(2))^(- 1)* CylinderU(a, t), t = 0..infinity) = sqrt(Pi/2)*GAMMA((1)/(2)- a)*(x)^(- a -(3)/(2))* exp((1)/(4)*(x)^(2))*CylinderU(- a, x)
Integrate[Exp[-Divide[1,4]*(t)^(2)]*(t)^(- a -Divide[1,2])*((x)^(2)+ (t)^(2))^(- 1)* ParabolicCylinderD[- 1/2 -(a), t], {t, 0, Infinity}, GenerateConditions->None] == Sqrt[Pi/2]*Gamma[Divide[1,2]- a]*(x)^(- a -Divide[3,2])* Exp[Divide[1,4]*(x)^(2)]*ParabolicCylinderD[- 1/2 -(- a), x]
Failure Aborted Skipped - Because timed out Skipped - Because timed out